PERAN KEPALA DESA DALAM PELAKSANAAN DANA DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 TENTANG PENGELOLAAN DANA DESA DI KABUPATEN PELALAWAN - Zulheri Zulheri; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a region with a decentralized government system, national development. In a village, there are several apparatuses that carry out all activities related to the village, and one of the village officials who has an important function in the continuity of activities in the village scope is the village head. In carrying out his duties, the village head only coordinates with the local camat and is only responsible for running the village government, implementing village development, fostering village community and empowering village communities. The village head has duties and functions for the welfare of the local community, including establishing policies regarding the implementation of, establishing policies for managing village property, taking actions that result in expenditure on the burden, establishing PPKD, approving DPA, DPPA and DPAL, approving RAK village and approving SPP. As for the purposes of writing this thesis, namely: First, to determine the function of the village head in implementing village funds in Pelalawan Regency, Second, to find out what efforts the village head can make to anticipate the misuse of village funds in Pelalawan Regency. This type of research is sociological law research, sociological, namely research on the effectiveness of the current law. Sources of data used in this study are primary data, secondary data and tertiary data. From the results of this study it can be concluded that the function of the village head in implementing village funds based on the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Fund Management in Pelalawan Regency can be said to be quite good in its implementation. Then related to the efforts that can be made by the village head to prevent misuse of village funds, including implementing the principles of transparency, accountability and participation in order to create better management of village funds. Keywords: Village Head - Duties and Functions - Village